PENINGKATAN INOVASI KERIPIK PISANG CURUG SULANJANA KECAMATAN GUNUNG SARI KABUPATEN SERANG - Claudius, Mikhael; Ruhiyat, Ramdan; Apendi, Apendi; Nurmala, Dewi Shofia; Sitorus, Sulastri (Batara Wisnu : Indonesian Journal of Community Services, 2021)
This Student Work Community Services Program aims to improve the people skill of Curug Sulanjana Village, Gunung Sari, Serang Regency. The partners of this activity are the community of Banana Chips, which is income second in this village apart from coconut and melinjo. The problem faced is the lack of innovation in Banana Chips processing. They are implementing this service through (1) survey every banana chips craftsman(2) training in making chips of various flavors. The result of this program is an increase in the knowledge and skills of the community in processing or making innovations in making Banana Chips. As a result from this program is expected to improve the community economy, especially the residents of Curug Sulanjana Village